Helminthiasis and Factors Affecting Nutritional Status of Pregnant Women at Karang Anyar Health Center Jati Agung, South Lampung: Helminthiasis dan Faktor yang Mempengaruhi Status Gizi Ibu Hamil di Puskesmas Karang Anyar Jati Agung Lampung Selatan - Hardianto, Devina; Suwandi, Jhons Fatriyadi; Zuraida, Reni; Setyaningrum, Endah (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
Nutrition in pregnancy is needed for fetal growth and development. Insufficient nutrition has the risk of causing Chronic Energy Deficiency (CED). The CED rate among pregnant women in Indonesia is 17.3% and in Lampung Province it is 13.6%. Nutritional status is influenced by nutritional intake and helminthiasis infection. Apart from that, there are other factors such as social determinants of health, namely economics, education, employment and age. This research uses a cross-sectional research design. The research sample was 86 pregnant women. Data collection was carried out using a questionnaire, measurement of Upper Arm Circumference (MUAC), and examination of feces using the formol ether sedimentation method. Bivariate analysis used chi square, Fisher, and Mann Whitney. The results of the study showed that there was a significant relationship between helminthiasis (p = 0.009), education (p = 0.023), and per capita income (p < 0.001) with the nutritional status of pregnant women. Meanwhile, for other variables (knowledge about helminthiasis, preventive behavior, age, and occupation) there was no significant relationship (p > 0.05). Helminthiasis is related to the nutritional status of pregnant women, so active screening is needed for the incidence of helminthiasis in pregnant women in the working area of the Karang Anyar Community Health Center, Jati Agung District, South Lampung Regency.